“During the pandemic, the sense of Ubuntu was fantastic”: a participatory research study commemorating community mobilisation - Ocholla, Diana Atieno (Graduate School of Business (GSB), 2026)
The COVID-19 pandemic will forever be etched into the world's collective memory as a defining event of our generation as the ramifications will be felt and experienced long into the future. To understand the effects and learn from the experiences of a community organization in a pandemic, the research question for this study was ‘What are the experiences and perceived effects of a community organisation engaging in a commemorative arts-based process for social innovation during a pandemic?'. The research methodology of this study was qualitative participatory research and it was conducted in Cape Town, South Africa, with members of the Woodstock Community Action Network. Data were collected virtually from seven participants through an online meeting (n=1), one-to-one interviews (n=7), online workshops (n=5), and a focus group (n=1) from April 2021-October 2021. Although there is significant literature on collective memory, commemoration, and community mobilisation, there is limited literature on these aspects in relation to the COVID-19 pandemic, South African Community Action Networks (CANs), as well as arts-based methods for commemoration and remote participatory research. The findings that emerged were presented under the following themes: 1) Addressing mental health and wellbeing challenges, 2) Empowerment within place, 3) Commemoration of the COVID-19 pandemic, 4) Heightened awareness of social inequity, and 5) Agency development through collaborative video. The significance of this research study was that it provided a means to understand what motivated community mobilisation to occur through focusing on documenting the experiences of Woodstock CAN members. In addition, the study demonstrated how the CAN as a social innovation, was already engaged in its own form of commemoration practice. Lastly, the video became a way to commemorate more tangibly and as a result, acted as social innovation tool in practicing agency and collaboration.